Multi-scale Hydrodynamics of Multiphase Flow in Vapour-Liquid Separation Processes - Mahadika Priyambodo, Muhammad Dary (Curtin University, 2023)
In this thesis, the underlying fluid dynamics of two components in a vapour liquid separator, that includes the inlet diverter and the knitted mesh pad was investigated. For the inlet diverter, the hydrodynamics of an existing and a novel inlet diverter design was investigated. For the knitted mesh pad, the research was focused on understanding the hydrodynamics of droplet capture on thin wires.